Data engineering for data-driven marketing - Balusamy, Balamurugan; Grover, Veena; Nallakaruppan, M. K. (Emerald Publishing Limited, 2025)
In the digital age, data has become the cornerstone of effective marketing strategies. Data Engineering for Data-Driven Marketing explores the vital intersection of data engineering and marketing, providing a comprehensive guide to harnessing the power of data for successful and impactful campaigns. Offering a thorough exploration of the symbiotic relationship between data engineering and modern marketing strategies, Data Engineering for Data-Driven Marketing uses a strategic lens to delve into methodologies of collecting, transforming, and storing diverse data sources. With real-world case studies actionable insights, the chapters within navigate the reader through the intricate process of building robust data pipelines, optimizing data quality, and implementing real-time processing techniques, all tailored to elevate marketing campaigns through precision targeting, customer personalization, and predictive modelling.
Includes index.
Keywords: MarketingData processing.; Business & Economics -- Marketing -- General.; Sales and marketing.; elektronické knihy; electronic books